Baso Aci Tata Snack goes to marketplace for smart city concept in Kediri - Djunaedi Djunaedi; Angga Rizka Lidiawan; Nursamsu Nursamsu; Edi Sinengko; Rima Novita Almatari (Community Empowerment, 2022)
The Kediri Government encourages the Smart City concept to be applied by all its people. The smart city concept also influenced Baso Aci Tata Snack to change its marketing method which initially used traditional methods to modern ways using sophisticated technology. Baso Aci Tata Snack is one of the MSMEs in Kediri City engaged in the culinary sector. The purpose of this service activity is to encourage MSME players of Baso Aci Tata Snack to have wise and effective knowledge about the use of digital media (marketplace) in their marketing activities so that their sales turnover can increase. The method used in this activity is the survey method. The results achieved in this activity are the knowledge and understanding of employees and owners of Baso Aci Tata Snack regarding the use of technology in determining strategies to go to marketplace. This service activity is very useful for Baso Aci Tata Snack because it can increase the profit to be obtained besides that the training carried out can increase the productivity of Baso Aci Tata Snack so as to improve employee welfare.